2020
DOI: 10.1016/j.seizure.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Patients self-mastery of wearable devices for seizure detection: A direct user-experience

Abstract: wearable devices aimed at detecting seizures are rapidly emerging. Continuous collection and optimal data quality are paramount to guarantee the acquisition of clinically meaningful data. It is still unknown how successfully patients can self-manage new technologies and which factors have an impact on this. We assessed the performance of patients managing a wrist-worn device. Method: patients wearing a wrist-worn device received a single training session to perform 5 tasks: (1) fitting the device correctly; (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Semi-structured interviews of people with epilepsy following a short trial with wearables in the hospital revealed preferences for wireless, small size, comfortable devices that can be used without support [10]. Another quantitative study focusing on self-managing a wrist worn device identified differences in coping with new technologies among participants [20]. These digital inequalities are strongly related to illness-perception-related factors (e.g., perceived disease timeline and personal control) and should be considered during implementation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-structured interviews of people with epilepsy following a short trial with wearables in the hospital revealed preferences for wireless, small size, comfortable devices that can be used without support [10]. Another quantitative study focusing on self-managing a wrist worn device identified differences in coping with new technologies among participants [20]. These digital inequalities are strongly related to illness-perception-related factors (e.g., perceived disease timeline and personal control) and should be considered during implementation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another quantitative study focusing on self-managing a wrist worn device identified differences in coping with new technologies among participants [20]. These digital inequalities are strongly related to illness-perception-related factors (e.g., perceived disease timeline and personal control) and should be considered during implementation [20].…”
Section: Discussionmentioning
confidence: 99%
“…For assisting the physically impaired, there are numerous wearable devices to help improve quality of life, such as hearing aids (ear-to-ear communication) [ 117 , 118 ]; devices for disability assistance, e.g., muscle tension monitor [ 119 ]; muscle tension stimulation [ 120 ]; wearable assistive devices for the blind [ 121 , 122 , 123 , 124 ]; devices for speech impairment [ 125 , 126 ]; artificial/wearable limbs [ 127 , 128 , 129 ]; and exoskeleton suits [ 130 ]. Other examples that can be used by the elderly, or by Alzheimer’s or epilepsy patients, include wearables for fall detection [ 131 , 132 , 133 ] and seizure detection [ 134 , 135 ], and gyroscopes [ 136 ] and accelerometers [ 137 ] for localization monitoring. Examples of implantable devices include pacemakers [ 138 ] and implantable cardioverter defibrillators (ICD) [ 139 ], and implanted actuator [ 140 , 141 ].…”
Section: Kpis For Specific 5g-healthcare Use Casesmentioning
confidence: 99%
“…Nonetheless, interest in continuous real-time monitoring and alarms has increased, especially in patients with a high seizure frequency and concomitant risk of SUDEP (20), where high rates of daily false alarms would become unbearable for those most affected. Nonetheless, it was shown that a system could possibly permit users to tune their sensitivity and false positive rates (122), allowing to adjust for the patients' individual preferences of control, which might be quite different (123).…”
Section: User Expectations and First Experiences With Device Implementationmentioning
confidence: 99%
“…Furthermore, rapidly adapting to the device when prompted, such as charging or even changing the battery, could create obstacles for efficient use. Recently, a study examining a wrist-worn device demonstrated that only 50% of patients were able to fully and independently control it, whilst others needed both appropriate support and training, and a subgroup of patients (13.3%) required constant supervision (123). In several devices, users have identified constraints early on.…”
Section: User Expectations and First Experiences With Device Implementationmentioning
confidence: 99%